Study on the three-dimensional numerical simulation of concentrated brine dispersal processes in estuarine bays - Xue, Huaiyuan; Shi, Hongyuan; Zhan, Chao; Wang, Qing; Li, Yan; You, Zaijin (Frontiers in Marine Science, 2024)
As a new type of liquid discharged into the sea, concentrated brine exhibits complex mixing and stratification patterns due to changes in its density and hydrodynamic properties. This complexity impacts salinity transmission and can result in brine intrusion disasters, directly affecting both ecosystem and human life. This research adopted brine discharge into Dingzi Bay, Shandong Peninsula, a typical estuarine bay, as a case study. 3D convective diffusion numerical simulation techniques were applied to investigate the pathways, salinity rise, impact range, and overall effects on brine dispersal in marine water environments under the combined influence of river flow and tides. The results indicated the followings: (1) Significant spatial variations were observed in flow velocities within Dingzi Bay, with higher velocities near Xiang Island (where river flow turned into the bay) and at bay mouth; (2) The brine discharge point is influenced by complex hydrographic terrain and the combined effects of river flow and tidal movements, resulting in the formation of a high salinity area at the base of the discharge point, where salinity increases by more than 4 PSU within a 100-meter radius.; (3) During high tides, high-concentration brine was clearly transported upstream along the tidal channel, with a salinity increase of ≥3psu covering an area of 5.72×104 m2, extending up to 270 m upstream and 180 m downstream. Brine discharge led to significant mixing of concentrated seawater with seawater within the bay, altering the spatial and temporal distributions of salinity in Dingzi Bay and consequently affecting local sensitive marine species and water environment safety. This study systematically investigated the process of brine discharge into the ocean and its impact range. It was found that discharging brine in areas with higher currents promotes the mixing and dispersion of brine. Additionally, a seasonal discharge plan should be established to avoid discharges during periods of low runoff (such as winter) to minimize negative impacts on aquatic ecosystems and promote the health and diversity of marine ecosystems.